OPTIMIZING ZISWAF POTENTIAL: STRATEGIES OF BANK SYARIAH INDONESIA IN PROMOTING SUSTAINABLE BUSINESS GROWTH - Febrina, Lis; Nurwahidin; Hannase, Mulawarman; Nafis, M. Cholil; Fatwa, Nur; Muttaqin, Mohammad Izdiyan; Zainal, Veithzal Rivai (International Journal of Social Service and Research, 2024)
This research aims to determine the provincial priorities for the development of the mosque-based ZISWAF ecosystem by Bank Syariah Indonesia (BSI). This study employs a descriptive qualitative approach, focusing on texts, expressions, and behaviors of resource persons to explore the potential of mosques and the potential for economic and financial empowerment of the people. The study uses a structured interview method to identify key areas on the islands of Java and Sumatra, specifically highlighting East Java, West Java, Jakarta, Aceh, and South Java, as well as additional regions like East Kalimantan, South Sulawesi, and Bali. The results of the study also show that there are differences, advantages, and disadvantages of UPZ and MPZ both in terms of legality, institutional, work patterns, operations, sustainability, and fund distribution flows. There are four clusters of challenges faced by Bank BSI in efforts to develop the mosque and mosque ecosystem in Indonesia, namely, the human resources of amil and nazhir mosques, worshippers and residents around mosques (government regulations and budgets), and the legality of mosque LPZs (local government budgets). The study also shows that there is a significant difference in the quality of mosque management based on dimensions, variables, and indicators on the existing mosque index. It is hoped that the use of this instrument can make it easier for Bank FSI to develop a mosque and its ecosystem for the progress and welfare of people and the nation.